2014
DOI: 10.1101/gad.245670.114
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila TRF2 is a preferential core promoter regulator

Abstract: Transcription of protein-coding genes is highly dependent on the RNA polymerase II core promoter. Core promoters, generally defined as the regions that direct transcription initiation, consist of functional core promoter motifs (such as the TATA-box, initiator [Inr], and downstream core promoter element [DPE]) that confer specific properties to the core promoter. The known basal transcription factors that support TATA-dependent transcription are insufficient for in vitro transcription of DPE-dependent promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 55 publications
2
52
0
3
Order By: Relevance
“…73 Interestingly, MEME analysis performed on the top TRF2-bound genes revealed enrichment of the DPE motif, while no enriched motif was identified in the least TRF2-bound genes. 74 Drosophila short TRF2 was recently identified by a biochemical complementation analysis as an enriched factor in fractions that support DPEdependent transcription. 74 Microarray analysis of Drosophila S2RC cells that overexpress inducible short TRF2 identified multiple DPE-dependent targets.…”
Section: Tbp-related Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…73 Interestingly, MEME analysis performed on the top TRF2-bound genes revealed enrichment of the DPE motif, while no enriched motif was identified in the least TRF2-bound genes. 74 Drosophila short TRF2 was recently identified by a biochemical complementation analysis as an enriched factor in fractions that support DPEdependent transcription. 74 Microarray analysis of Drosophila S2RC cells that overexpress inducible short TRF2 identified multiple DPE-dependent targets.…”
Section: Tbp-related Factorsmentioning
confidence: 99%
“…74 Drosophila short TRF2 was recently identified by a biochemical complementation analysis as an enriched factor in fractions that support DPEdependent transcription. 74 Microarray analysis of Drosophila S2RC cells that overexpress inducible short TRF2 identified multiple DPE-dependent targets. In vitro transcription followed by primer extension analysis of 4 TRF2 target genes (pvf2, sodh-2, bgm and inx3) indicated that their transcription was highly dependent on an intact DPE motif.…”
Section: Tbp-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed co-activation of gt reporter genes by the Bicoid transcription factor using firefly luciferase reporter genes driven by either a DPE-dependent (containing mTATA) or a TATA-dependent (containing mDPE) version of the gt transcriptional control region from Ϫ2031 to ϩ40 relative to the RNA start site (83). S2Rϩ cells were transfected with either a DPE-dependent or a TATA-dependent gt reporter construct as well as an expression vector for Bicoid and/or dCBP.…”
Section: The Regions Containing Both the Homeodomains And The N Termimentioning
confidence: 99%